Seraphina - Hartman, Rachel (New York : Random House, 2012)
In a world where dragons and humans coexist in an uneasy truce and dragons can assume human form, Seraphina, whose mother died giving birth to her, grapples with her own identity amid magical secrets and royal scandals, while she struggles to accept and develop her extraordinary musical talents
Keywords: Identity (Philosophical concept) -- Fiction; Self-actualization (Psychology) -- Fiction; Dragons -- Fiction; Music -- Fiction; Courts and courtiers -- Fiction; Fantasy; Identity (Philosophical concept) -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Dragons -- Juvenile fiction; Secrets -- Juvenile fiction; Music -- Juvenile fiction; Courts and courtiers -- Juvenile fiction; Fantasy fiction